A Comprehensive Review on Ratha taila for Management of Rathagaya namely Infant/ Childhood Atopic Dermatitis - Dushmantha, W.K.T.; Herapathdeniya, S.K.M.K. (SLJIM, 2021)
Ayurveda is mainly focused on preventive and curative aspects of health. Ratharoga/ Rathagaya is a disease that commonly occurs within infants and children, which can correlate with the Charmadala in Ayurveda and atopic dermatitis in Paediatrics. According to Traditional Medicine, Ratha taila is the commonest external application for Rathagaya with Ratha kalka internally. This study aims to supply a comprehensive review on Ratha taila by analyzing the suitability of the ingredients theoretically, through their Ayurveda and modern pharmacodynamic properties and actions for Rathagaya with the modern correlation to atopic dermatitis. The review was conducted by referring related textbooks and online research articles and by analyzing the pharmacodynamic properties and actions listed in each ingredient of Ratha taila. The recipe mentioned under the 20th chapter of the 1st volume of the Ayurveda Pharmacopeia was used. Upon analysis of the ingredients and the base oil of Ratha taila, it comprises of Pitta shamaka, Tvachya and Raktha shodhaka actions at a higher ratio owing to their Rasa, Guna, Veerya, Vipaka and Dosha karma comparatively. As per modern medicine, pharmacological actions such as anti-inflammatory, antimicrobial and antioxidant actions present in these ingredients are vital to skin health. Ratha taila contributes to pacify the other Dosha since Kushtha roga (skin disorders) have Tridosha origin. It can be concluded that Ratha taila is therapeutically useful in the management of Rathagaya as a unique external application on the skin.
Keywords: Ratha roga; Atopic dermatitis; Ratha taila; Pitta dosha; Sri Lankan Traditional Medicine